2019
DOI: 10.1002/car.2561
|View full text |Cite
|
Sign up to set email alerts
|

What are the Optimal Combinations of Parenting Intervention Components to Reduce Physical Child Abuse Recurrence? Reanalysis of a Systematic Review using Qualitative Comparative Analysis

Abstract: Parenting interventions are widely used to reduce physical child abuse, but evidence for their effectiveness is mixed, partly because standard methods for synthesising the effectiveness of interventions do not address complex causation. We addressed this by using qualitative comparative analysis to understand pathways to effectiveness in social learning theory‐based parenting interventions. After a systematic search of nine databases and independent and duplicate study selection, we included 14 interventions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…Programs reviewed included the Incredible Years Parenting Program ( 30 ), Triple-P Positive Parenting Program ( 31 ), Parent Management Training Oregon Model (PMTO) ( 32 ), Parent-Child Interaction Therapy ( 33 ), Parent Corps ( 34 ), and ACT Raising Safe Kids ( 35 ) from high-income countries and Sinovuyo ( 36 ), Parents Make a Difference ( 15 ), and Projecto Paceria ( 37 ) from low and middle-income countries (LMIC). We also examined reviews and meta-analyses of the common core components of parenting interventions to identify the components that lead to more effective parenting interventions to prevent and reduce children's externalizing behavior ( 38 40 ) and to prevent and treat parents' use of violence against children ( 41 43 ). As the parenting intervention is planned as a complementary program to the Irie Classroom Toolbox, we also identified components from the Irie Classroom Toolbox that would be applicable to parents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Programs reviewed included the Incredible Years Parenting Program ( 30 ), Triple-P Positive Parenting Program ( 31 ), Parent Management Training Oregon Model (PMTO) ( 32 ), Parent-Child Interaction Therapy ( 33 ), Parent Corps ( 34 ), and ACT Raising Safe Kids ( 35 ) from high-income countries and Sinovuyo ( 36 ), Parents Make a Difference ( 15 ), and Projecto Paceria ( 37 ) from low and middle-income countries (LMIC). We also examined reviews and meta-analyses of the common core components of parenting interventions to identify the components that lead to more effective parenting interventions to prevent and reduce children's externalizing behavior ( 38 40 ) and to prevent and treat parents' use of violence against children ( 41 43 ). As the parenting intervention is planned as a complementary program to the Irie Classroom Toolbox, we also identified components from the Irie Classroom Toolbox that would be applicable to parents.…”
Section: Methodsmentioning
confidence: 99%
“…For programs targeting child externalizing behavior, building a positive parent-child relationship through nurturing, positive and sensitive interactions, the use of praise and positive reinforcement, emotional communication, and learning appropriate discipline methods such as time-out and consequences have been shown to be important components ( 38 , 40 ). For programs targeting child maltreatment, learning non-violent discipline approaches, daily child-led play, and parental self-management skills have been shown to be most effective ( 41 , 42 ). In terms of the process of delivering the content, the most effective programs are delivered in a non-stigmatizing way, focus on building parents' self-confidence and involve modeling, rehearsal and practice, supportive feedback, homework assignments, and problem-solving activities ( 38 , 42 , 43 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is clear that teachers require additional support to further reduce the use of violence against children. A qualitative review of parenting interventions aimed at reducing child abuse found that teaching parental self-management strategies was an important component of effective programmes [42]. Explicit attention to promoting teachers’ self-regulatory capacities may help to further reduce teachers’ use of violence against children [43].…”
Section: Discussionmentioning
confidence: 99%
“…We start the issue with a reanalysis of a systematic review of parenting interventions to reduce physical child abuse recurrence by G. J. Melendez‐Torres and colleagues (). These authors point out that while parenting interventions are widely used to reduce physical child abuse, the evidence for their effectiveness is mixed.…”
Section: Public Health: Parenting Physical Abuse Trafficking and Exmentioning
confidence: 99%